Percepções dos professores de língua portuguesa de Barra do Garças/MT sobre as práticas de multiletramento no retorno às aulas presenciais - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This research aims to investigate the perceptions of high school teachers from the state public school system in Barra do Garças - MT, about multilingual practices used, especially in the context of returning to face-to-face teaching, after the emergency remote teaching period, during the Covid 19 pandemic. My interest in this topic arose from my concerns about how high school teachers perceive multilingual practices and the use of digital technologies when returning to face-to-face classes. So, what tools and resources did they continue to use after the Covid-19 pandemic? Did they have training and access to them? After the period of emergency remote teaching, what was the process of change like in the face of difficulties and challenges? Were the teachers able to relate multilingualism and digital technologies to reading and understanding texts? Based on these questions, I'm looking for answers so that other education professionals, especially teachers, can also reflect on the discussions I'm building in this research. The method used is netnography, also known as ethnography for the study of online cultures and communities, and as research tools I opted for an online questionnaire, applied using Google Forms. The research participants are high school teachers from state public schools in Barra do Garças/MT, considering the practices developed between the years 2021 and 2022. The studies are undertaken by Aguiar (2019), Baratto (2013), Bakhtin ( 2011) (2003) (1981), Bogdan; Boklen (1994), Castells (1999), Cope; Kalantzis (2010), Duboc (2012), Freitas (2019), Flick ( 2009), Minayo (2014), Moran (2000), Pinheiro (2016), Prodanov ( 2013), Rojo (2012), Rojo; Moura (2012), Ribeiro (2012) (2009); Santos; Santos; Cavalcanti (2020), Soares (2000), among others, who brought contributions to the research. This study analyzed the reflections and new praxologies in relation to multilearning, teacher training and digital technologies used by Portuguese language teachers after the Covid 19 pandemic, showing them the importance of improvement and continuous use in a strategic way for learning.
Perceptions of portuguese language teachers in Barra Do Garças/MT about multilearning practices on their return to face-to-face classes
Keywords: Multiletramento; Professores; Tecnologia digital; Ensino remoto emergencial; Multilearning; Teachers; Digital technology; Emergency remote teaching; LINGUISTICA::LINGUISTICA APLICADA